Evidence that Modifications of Lp(a) In Vivo Inhibit Plasmin Formation on Fibrin - Soulat, Thierry; Loyau, Stéphane; Baudouin, Veronique; Durlach, Vincent; Gillery, Philippe; Garnotel, Roselyne; Loirat, Chantal; Anglés-Cano, Eduardo (Thrombosis and Haemostasis, 1999)
In the present study we have investigated the effect of individual variations in the concentration of Lp(a) on plasmin formation at the surface of fibrin. The plasma Lp(a) concentrations from 20 nephrotic children were high at flare-up of the disease (0.43 ± 0.45 g/l) and decreased progressively with remission at both 6 weeks (0.28 ± 0.24 g/l) and 6 months (0.24 ± 0.288 g/l). In contrast, the concentration of plasminogen showed an inverse variation, with low values at flareup (1.27 ± 0.34 μM) and normal values at remission (1.66 ± 0.17 μM at 6 weeks and 1.99 ± 0.21 μM at 6 months). An increase in plasmin formation (from 0.62 ± 0.49 to 0.73 ± 0.61, and 0.84 ± 0.75 pmol/well) and a decrease in apo(a) binding (from 5.45 ± 2.42 to 4.54 ± 2.12, and 3.93 ± 1.51 fmol/well) on the surface of fibrin, were concomitantly observed from flare-up to remission at 6 weeks and at 6 months, respectively. Values for plasmin formation parallel the amount of plasminogen bound. The low concentration of plasminogen found at flare-up may also have contributed to the increased binding of Lp(a) as indicated by a decrease in the maximal amount of Lp(a) bound (Bmax) to fibrin as a function of plasma plasminogen concentrations. Bmax was 1.51 fmol in the absence of plasminogen and decreased to 1.1 fmol and 0.93 fmol at respectively 1 and 2 μM of plasminogen. Altogether, these data constitute the first quantitative evidence indicating that plas-min formed at the surface of fibrin may vary with modifications of the concentration of Lp(a) in vivo.